Toward living neuroprosthetics: developing a biological brain pacemaker as a living neuromodulatory implant for improving parkinsonian symptoms. (8th June 2021) - Prox, Jordan; Seicol, Benjamin; Qi, Hao; Argall, Aaron; Araya, Neway; Behnke, Nicholas; Guo, Liang
Abstract: Objective. Therapeutic intervention for Parkinson's disease (PD) via deep brain stimulation (DBS) represents the current paradigm for managing the advanced stages of the disease in patients when treatment with pharmaceuticals becomes inadequate. Although DBS is the prevailing therapy in these cases, the overall effectiveness and reliability of DBS can be diminished over time due to hardware complications and biocompatibility issues with the electronic implants. To achieve a lifetime solution, we envision that the next generation of neural implants will be entirely 'biological' and 'autologous', both physically and functionally. Thus, in this study, we set forth toward developing a biological brain pacemaker for treating PD. Our focus is to investigate engineering strategies for creating a multicellular biological circuit that integrates innate biological design and function while incorporating principles of neuromodulation to create a biological mechanism for delivering high-frequency stimulation with cellular specificity. Approach. We engineer a 3D multicellular circuit design built entirely from biological and biocompatible components using established tissue engineering protocols to demonstrate the feasibility of creating a living neural implant. Furthermore, using 2D co-culture systems, we investigate the physiologically relevant parameters that would be necessary to further develop a therapeutic benefit of high-frequency stimulation with cellular specificity within our construct design. Main results. Our results demonstrate the feasibility of fabricating a 3D multicellular circuit device in an implantable form. Furthermore, we show we can organize cellular materials to create potential functional connections in normal physiological conditions, thus laying down the foundation of designing a high-frequency pacing system for selective and controlled therapeutic neurostimulation. Significance. The findings from this study may lead to the future development of autologous living neural implants that both circumvent the issues inherent in electronic neural implants and form more biocompatible devices with lifelong robustness to repair and restore motor functions, with the ultimate benefit for patients with PD.